Development of Fuzzy Logic Based Temperature Controller for Dialysate Preparation System - Pratondo Busono; Ario Fitrianto; Teguh Handoyo; Arief Barkah; Yaya Suryana; Riyanto Riyanto; Rony Febryarto (IAES Indonesia Section, 2015)
Preparing the dialysate temperature to the desiredlevel is a complicated task, since it has a large degree of time delayand nonlinear behaviour. In this work, embedded system fordialysate temperature controller was developed. It is based onimplementation of fuzzy logic controller software on STM32 F4development kit which consits of ARM Cortex M4Fmicrocontroller. The dialysate temperature was controlled byvarying the firing angle of the triac which is connected to theheater. The K-type thermocouple which is connected to AD595CQwas read and compared with the desire dialysate temperature.The fuzzification process was conducted prior to activate the fuzzyinference process. The power of the heater was adjusted based onthe output of the inference process until the desired watertemperatur was achieved. The system had been sucessfullydemonstrated for controlling the dialysate temperature.